2018
DOI: 10.1016/j.stem.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

PPM1D Mutations Drive Clonal Hematopoiesis in Response to Cytotoxic Chemotherapy

Abstract: SummaryClonal hematopoiesis (CH), in which stem cell clones dominate blood production, becomes increasingly common with age and can presage malignancy development. The conditions that promote ascendancy of particular clones are unclear. We found that mutations in PPM1D (protein phosphatase Mn2+/Mg2+-dependent 1D), a DNA damage response regulator that is frequently mutated in CH, were present in one-fifth of patients with therapy-related acute myeloid leukemia or myelodysplastic syndrome and strongly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
269
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(293 citation statements)
references
References 47 publications
18
269
2
4
Order By: Relevance
“…73 Similarly, human and murine hematopoietic cells with PPM1D mutations were shown to outcompete wild type cells after exposure to DNA-damaging agents. 74 Importantly, several studies now have shown that patients with CH and in particular CH-PD have significantly increased risks of developing myeloid neoplasia ( Figure 2C). Based on case-control studies, solid tumor patients with CH have an approximately 5-to 15-fold increased risk of developing t-MN.…”
Section: Ch and Risk Of Therapy-related Myeloid Malignanciesmentioning
confidence: 98%
“…73 Similarly, human and murine hematopoietic cells with PPM1D mutations were shown to outcompete wild type cells after exposure to DNA-damaging agents. 74 Importantly, several studies now have shown that patients with CH and in particular CH-PD have significantly increased risks of developing myeloid neoplasia ( Figure 2C). Based on case-control studies, solid tumor patients with CH have an approximately 5-to 15-fold increased risk of developing t-MN.…”
Section: Ch and Risk Of Therapy-related Myeloid Malignanciesmentioning
confidence: 98%
“…Interestingly, early detection of CHIP may predict risk of developing cardiovascular disease, with potentially actionable consequences. As well, PPM1D mutations are common in solid tumor patients who have received platinum therapy and appear to predispose to a secondary hematological malignancy . Screening for these mutations may also be of clinical benefit.…”
Section: When Should Screening Occur?mentioning
confidence: 99%
“…As well, PPM1D mutations are common in solid tumor patients who have received platinum therapy and appear to predispose to a secondary hematological malignancy. 71 Screening for these mutations may also be of clinical benefit. Further research is needed to better define the risks and benefits of broad-based screening for clonal hematopoiesis.…”
Section: When S Hould Screening O Ccur?mentioning
confidence: 99%
“…The very wide variation in VAFs observed between people is largely caused by the combined effects of chance (when a mutation arises) and fitness differences (how fast they expand). While cell-extrinsic effects are likely crucial in specific contexts such as chemotherapy 11,26,40,41 and acute infection 42,43 , the data from healthy individuals are quantitatively consistent with cell-intrinsic differences in fitness effects being the major determinants of the variation.…”
Section: A Simple Framework Explains Clonal Haematopoiesismentioning
confidence: 62%